Effect of soybean feeding in place of fish-meal on feed conversion efficiency and economics of pig farming - KUMAR, ASHOK; THAKUR, S; SINGH, S K (The Indian Journal of Animal Sciences, 2013)
The present study was camed on 27 and D growing pigiets, 3-to 4-month-old, readred on uniform housing and managemental condition at Pig Breeding Farm of Ranchi Veterinary College, Birsa Agricultural University, Ranchi, Bihar, with an objective to cut down the cost of feed per unit weight gain of pigs. Three types of concentrate mixtures were formulated for the study. First group (T1) having 6.5% fish-meal served as control, whereas, fish-meal of T2 and T3 was completely replaced by pressure cooked crushed soybean-meal. In addition to this, T3 group was supplemented with lysine and methionine @ 10g/100kg of concentrate mixture. Piglet of all the 3 groups were fed ad lib. for 13 weeks ofexperimental period and weekly body weight besides daily feed consumption were recorded.The intake of feed/kg gain in body weight in T1 T2 and T3 were 3.75 ± 0.18,3.65 ± 0.33 and 3.77 ± 0.26 kg, respectively, which did not differ significantly among themselves. The findings clearly indicated that feed conversion efficiency of ration containing soybean by replacing fish-meal completely was equally good. The cost (Rs/100kg) of pig grower ration containing soybean was lower (Rs 650.80 in T3 group) compared to fishmeal containing control ration (Rs 701.60). The cost of soybean containing diet was cheaper by 7.24 and 6.72% for T2 and T3 groups, respectively, compared to fish-meal containing diet T . The average cost of feed/kg gain in body weight was Rs 26.28, 23.49 and 24.67 for T1 T2 and T3 groups respectively. The feed cost per unit gain in body weight was lowered by 9.50% on diet containing soybean and 6.08% on soybean supplemented with lysine and methionine compared to fish-meal containing diet T1.